Wind loading on high-rise buildings and the comfort effects on the occupants. (February 2019) - Avini, Ramtin; Kumar, Prashant; Hughes, Susan J.
Graphical abstract: Highlights: Wind loads for tall buildings studied by codes and Computational Wind Tunnel (CWT). Design Standards gave rise to larger surface pressures than CWT estimates. Complex terrain led to more fragmented vortices in New York City. Shielding effect was crucial for depleting the mean component of the load. Building's low damping level resulted in surpassing comfort limits in some cases. Abstract: The design of low to medium-rise buildings is based on quasi-static analysis of wind loading. Such procedures do not fully address issues such as interference from other structures, wind directionality, across-wind response and dynamic effects including acceleration, structural stiffness and damping which influence comfort criteria of the occupants. This paper studies wind loads on a prototype, rectangular cross-section building, 80 m high. Computational Wind Tunnel (CWT) tests were performed using Autodesk Flow Design with the buildings located in London and New York City. The analysis included tests with and without the surrounding structures and manual computation of wind loads provided data for comparison. Comfort criteria (human response to building motion) were assessed from wind-induced horizontal peak accelerations on the top floor. As expected, analytical methods proved conservative, with wind pressures significantly larger than those from the CWT tests. Surrounding structures reduced the mean component of the wind action. As for comfort criteria, across-wind direction governed the horizontal accelerations with wind targeted on the building's narrow face. CWT tests provide a cheaper alternative to experimental wind tunnel tests and can be used as preliminary design tools to aid civil engineers, architects and designers with high-rise developments in urban environments.